Legal Regulation of Educational Activities in Public Schools - ROMANOVA, Svetlana A.; GULAYA, Tatyana M.; GERASIMENKO, Tatyana L. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
In the paper it notes: the quality of education is a series of systemic-social qualities and characteristics that define the system of education adopted requirements, social norms, the state educational standards. The authors believe that quality education depends on the quality of requirements (goals, standards and norms), quality resources (programs, personnel potential, contingent of entrants, logistics, Finance, etc.) and the quality of the educational process (scientific and educational activities, management, educational technology), which directly provide the training. The novelty of this work is that the country's accession to the Bologna process has resulted in the need for corresponding harmonization of the current quality assurance system of higher education to the commitments made. Quality assurance of higher education at the state level is achieved by development of normative-legal, organizational, methodological and other documents regulating the system of state quality control of education. The authors note that in the implementation of many activities that should contribute to quality assurance in higher education. The subject of the study is that the current quality assurance system (external expert evaluation of activities of higher education institutions) is now at the stage adaptation of the national system of quality assurance standards and guide lines for quality assurance in the European higher educatio narea. In particular, the formation of the monitoring system and definition of rating of higher educational institutions, which in the assessment activities of the University focuses on international indicators (indicators). Even today, some universities are turning to international accreditation agencies. The study's findings is that the system of legal acts regulating the functioning of higher education, while maintaining a certain level of state regulation of activities in the field of higher education, provides an opportunity to ensure greater compliance with the professional qualification level of training of specialists for the requirements of the social division of labor and mobility system of training of specialists on the labor market. At the same time, the analysis of normative-legal acts on higher education shows that, despite the progressive legal instruments adopted in recent years aimed at the development of the education system, they still characterized by inconsistency, ambiguity, and the impossibility of monitoring the implementation of certain provisions. For the solution of problems a rising in the process of quality management of higher education, the need for further improvement and development framework. Important measure to improve the quality of education and management is the implementation of quality management systems in higher education institutions.